Work difficulties, work restrictions, and disability benefits in people with functional seizures: A survey study - Jared Woodward; Ali A. Asadi-Pooya; Bridget Mildon; Benjamin Tolchin (Epilepsy & Behavior Reports, 2023)
Purpose: Functional seizures (FS) cause significant long-term disability and clinicians offer differing views on proper work restrictions and qualifications for disability benefits in this population. We assess the views and perspectives of experienced disability and work limitations in people living with functional seizures. Methods: Between (4/29/2020–1/13/2021) an open-access 21-item internet survey was conducted via FNDHope.org; allowing for people living with self-reported functional seizures to remark on topics of work difficulties, work restrictions, qualifications for disability benefits, and driving. Demographic information was collected, and univariate and multivariate logistic regressions were used to evaluate potential predictors of current employment status. Results: One hundred eighteen (118) responses were received, of which 92 (84.4%) completed > 50% of the survey; they were predominantly (92%) female. Most respondents (88%) reported some personal difficulty at work and nearly all (99%) believed that others with FS would experience difficulties in the workplace. A majority (71%) felt that work restrictions should apply to people living with active FS, at least in certain lines of work. Most (64%) felt people with FS should qualify for disability benefits; however, 35% stated work accommodations or a new job compatible with FS was more appropriate. Of those who felt people with FS should qualify for disability, 60% thought recipients should remain eligible for disability while symptomatic and 38% felt benefits should be lifelong. In univariate and multivariate logistic regressions, older age was predictive of unemployment (univariate OR 0.95 ± 0.02, 95% CI 0.92–0.98, p-value 0.002). Conclusion: Our results suggest that work difficulties are common in people with FS, with older age being a predictor of unemployment. A majority of people with FS support work restrictions for those with their disorder, at least in some lines of work. In comparison to a prior study of clinicians, a higher percentage of people with FS supported work restrictions. These results may help facilitate productive discussions between people with FS, providers, and policymakers regarding appropriate work and disability limitations.